Wearable and telemedicine innovations for Olympic events and elite sport - Muniz-Pardos, B.; Angeloudis, K.; Guppy, F. M.; Keramitsoglou, I.; Sutehall, S.; Bosch, A.; Tanisawa, K.; Hosokawa, Y.; Ash, G. I.; Schobersberger, W.; Grundstein, A. J.; Casa, D. J.; et al. (The Journal of Sports Medicine and Physical Fitness, 2021)
Rapid advances in wearable technologies and real-time monitoring have resulted in major inroads in the world of recreational and elite sport. One such innovation is the application of real-time monitoring, which comprises a smartwatch application and ecosystem, designed to collect, process and transmit a wide range of physiological, biomechanical, bioenergetic and environmental data using cloud-based services. We plan to assess the impact of this wireless technology during Tokyo 2020, where this technology could help characterize the physiological and thermal strain experienced by an athlete, as well as determine future management of athletes during a medical emergency as a result of a more timely and accurate diagnosis. Here we describe some of the innovative technologies developed for numerous sports at Tokyo 2020 ranging from race walking (20 km and 50 km events), marathon, triathlon, road cycling (including the time trial event), mountain biking, to potentially team sports played outdoors. A more symbiotic relationship between sport, health and technology needs to be encouraged that harnesses the unique demands of elite sport (e.g., the need for unobtrusive devices that provide real-time feedback) and serves as medical and preventive support for the athlete`s care. The implementation of such applications would be particularly welcome in the field of medicine (i.e., telemedicine applications) and the workplace (with particular relevance to emergency services, the military and generally workers under extreme environmental conditions). Laboratory and field-based studies are required in simulated scenarios to validate such emerging technologies, with the field of sport serving as an excellent model to understand and impact disease.